2014
DOI: 10.1137/130920824
|View full text |Cite
|
Sign up to set email alerts
|

Finite Volume Modeling of Poroelastic-Fluid Wave Propagation with Mapped Grids

Abstract: Abstract. In this work we develop a high-resolution mapped-grid finite volume method code to model wave propagation in two dimensions in systems of multiple orthotropic poroelastic media and/or fluids, with curved interfaces between different media. We use a unified formulation to simplify modeling of the various interface conditions -open pores, imperfect hydraulic contact, or sealed pores -that may exist between such media. Our numerical code is based on the clawpack framework, but in order to obtain correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…However, our results from the advection of a nonlinear vortex test also revealed that the order of accuracy is severely degraded when using the circular mapping proposed by Calhoun et al (2008), i.e., the grid smoothness directly impacts the achievable order of accuracy of the scheme. Our finding agrees with results obtained by Lemoine & Ou (2014), who used a modified version of grid mappings suggested by Calhoun et al (2008). Lemoine & Ou also achieved roughly first-order convergence on these nonsmooth grid mappings.…”
Section: Discussionsupporting
confidence: 91%
“…However, our results from the advection of a nonlinear vortex test also revealed that the order of accuracy is severely degraded when using the circular mapping proposed by Calhoun et al (2008), i.e., the grid smoothness directly impacts the achievable order of accuracy of the scheme. Our finding agrees with results obtained by Lemoine & Ou (2014), who used a modified version of grid mappings suggested by Calhoun et al (2008). Lemoine & Ou also achieved roughly first-order convergence on these nonsmooth grid mappings.…”
Section: Discussionsupporting
confidence: 91%
“…where μ and λ correspond to the usual Laméc o e ffi c i e n t s ,Q and M are Biot's original notation defined in 95 equations (18) and (19) below, and I denotes the identity tensor. As usual, under the assumption that the fluid does not support shear stress, one may interpret μ as the dry matrix shear modulus μ fr .…”
Section: Poroelastic Hooke's Lawsmentioning
confidence: 99%
“…A broad ranging review of computational poroelasticity is given 30 in [12]. We refer also to the recent papers [13,19,20] who work in a finite volume setting. DG methods have been implemented previously for poroelastic wave propagation; we mention [14,15] who worked in the time domain, while the recent paper [16] considers frequency domain solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can also be extended to other geometries and the Clawpack software (with adaptive mesh refinement) can be applied in situations where a logically rectangular grid can be mapped to a quadrilateral two-dimensional grid. This can include situations in which the interface is circular or of other smooth shape lacking corners using the sort of mappings proposed in [14], which have been used for elastic and poroelastic wave propagation problems in the work of Lemoine [51,52]. Extension of the methods proposed in this paper to such cases is currently under way and will be reported elsewhere [25].…”
Section: Transverse Riemann Solversmentioning
confidence: 99%